2004
DOI: 10.1029/2004gl021158
|View full text |Cite
|
Sign up to set email alerts
|

The influence of data assimilation on the age of air calculated with a global chemistry‐transport model using ECMWF wind fields

Abstract: The age of air is a useful integrated quantity that represents transport processes. Most atmospheric models underestimate the age of air, especially when wind fields from data assimilation systems are used. Nonetheless data assimilation is necessary to provide realistic winds. The European Centre for Medium‐Range Weather Forecasts (ECMWF) uses different assimilation procedures with various forecast periods, where forecasting allows the model to recover from the non‐physical adjustments of the assimilation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 23 publications
8
50
0
Order By: Relevance
“…Using forecast rather than analyzed winds reduces the dispersion (Meijer et al 2004), as does the use of shorter intervals between analyses (Legras et al 2005). These findings suggest that the spurious dispersion found by using analysed winds at 6-hour intervals results from effectively ''freezing'' the noise introduced in the assimilation process, introducing artificially long correlation times in the winds by interpolating between 6-hour intervals.…”
Section: Transport In Modelsmentioning
confidence: 93%
“…Using forecast rather than analyzed winds reduces the dispersion (Meijer et al 2004), as does the use of shorter intervals between analyses (Legras et al 2005). These findings suggest that the spurious dispersion found by using analysed winds at 6-hour intervals results from effectively ''freezing'' the noise introduced in the assimilation process, introducing artificially long correlation times in the winds by interpolating between 6-hour intervals.…”
Section: Transport In Modelsmentioning
confidence: 93%
“…Radiative heating rates (Q) are applied as vertical velocity in a quasi-isentropic trajectory model in the stratosphere to avoid the noisy (Manney et al, 2005b) and too high vertical velocities of meteorological assimilations (Meijer et al, 2004;Scheele et al, 2005;Monge-Sanz et al, 2007). Such an approach can be employed in the stratosphere, where radiative processes are determining the slow mean meridional circulation (Andrews et al, 1987).…”
Section: Model and Methodsmentioning
confidence: 99%
“…The results are not very sensitive to this choice. Our method of computing the mean age differs significantly from the method used by Meijer et al (2004). He calculated the age spectrum, starting with a delta function between 10 • S and 10 • N below 200 hPa, and integrated the TM4 model for 20 years in order to estimate the age at 20 km altitude.…”
Section: Methods To Calculate the Age Of Airmentioning
confidence: 99%
“…In a recent study by Meijer et al (2004), the stratospheric age of air in a CTM (the TM4 model), driven by different data sets from the European Centre for Medium-Range Weather Forecast (ECMWF), was compared to the age of air, calculated from observations (Andrews et al, 2001). The results showed that in the extratropics at 20 km altitude the simulated age of air was about half that of the observationbased age.…”
Section: Introductionmentioning
confidence: 99%